2013
DOI: 10.1002/cam4.169
|View full text |Cite
|
Sign up to set email alerts
|

Chemoradiotherapy response in recurrent rectal cancer

Abstract: The efficacy of response to preoperative chemoradiotherapy (CRT) in recurrent versus primary rectal cancer has not been investigated. We compared radiological downsizing between primary and recurrent rectal cancers following CRT and determined the optimal size reduction threshold for response validated by survival outcomes. The proportional change in tumor length for primary and recurrent rectal cancers following CRT was compared using the independent sample t-test. Overall survival (OS) was calculated using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 27 publications
2
16
0
1
Order By: Relevance
“…7,25 Preoperative tumor volume reduction, which can be caused by preoperative radiotherapy, increased the likelihood of complete resections, 15 and volume reduction of >50% shows a survival benefit. 24 also, several studies have shown that complete surgical resections provide a significant survival advantage compared with incomplete resections. [11][12][13]15,17,19,21,[26][27][28][29][30][31][32] in the included studies, most recurrences were treated with chemoradiation instead of radiotherapy alone.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…7,25 Preoperative tumor volume reduction, which can be caused by preoperative radiotherapy, increased the likelihood of complete resections, 15 and volume reduction of >50% shows a survival benefit. 24 also, several studies have shown that complete surgical resections provide a significant survival advantage compared with incomplete resections. [11][12][13]15,17,19,21,[26][27][28][29][30][31][32] in the included studies, most recurrences were treated with chemoradiation instead of radiotherapy alone.…”
Section: Discussionmentioning
confidence: 98%
“…[33][34][35][36] a recent study demonstrated good responses and improved survival in patients who were treated with reirradiation with concurrent Ctx in lRRC patients compared with radiotherapy only. 24 So, although the evidence is weak, chemoradiation seems to be the preferred treatment option to reirradiate patients with lRRC.…”
Section: Discussionmentioning
confidence: 99%
“…Rectal cancer is a very common gastrointestinal cancer with a high malignancy rate and unknown etiology (1) . Even worse, rectal cancer is a leading cause of cancer-related deaths worldwide and may occur in younger people (2) .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the rates of postoperative complications had been reported to be up to 68% . Chemotherapy (CT) and further external beam radiation therapy (EBRT) may only provide palliative benefit . Conventional EBRT reirradiation can be risky as dose limiting normal tissues in pelvis such as the bowel or the bladder have often been treated to tolerance and further radiation may prove unsafe .…”
Section: Introductionmentioning
confidence: 99%